Analisis Potensi Incentive Tour di Kota Cirebon - Dian Fitriyana; Chondro Suryono (Pusat Penelitian Dan Pengabdian Masyarakat STIEPARI Semarang, 2024)
The city of Cirebon has emerged as a tourism destination city that has a variety of beauties, both natural beauty, artificial beauty, culinary, art, history and so on. In business management, in order to support tourism needs, the city of Cirebon follows developments by having more than 30 tours and travel companies that manage local, inter-city and overseas tourism. Incentive tours are often used by large companies as a form of appreciation for the performance results of the person concerned. This activity is also believed to be able to support individual loyalty to the company for a certain period of time. This method has been practiced by many out-of-town companies who send incentive tours to the city of Cirebon as a form of appreciation. This research was conducted in the city of Cirebon through observation and literature study in data collection and using qualitative methods. The results of data collection are described in accordance with current conditions and circumstances. The results of this research provide an illustration that tour and travel has a very important role in the world of tourism because it is one of the spearheads in developing tourism as well as being a driving force for tourists so that it is easier to find the information they want and can buy the service products offered. However, marketing in the incentive tour sector is still very minimal and is only known through word of mouth, not through large-scale promotions. Tour and travel service providers only create incentive tour package concepts by request from companies that contact them. There have not been any public tour packages operating in the corporate market.